1955
DOI: 10.1172/jci103094
|View full text |Cite
|
Sign up to set email alerts
|

Potassium and Sodium Restriction in the Normal Human 1

Abstract: Restriction of potassium intake leads to depletion of body potassium, chiefly as a result of losses of potassium in the urine (1-3). The ability of the kidney to conserve potassium has been variously assessed. Tarail and Elkinton (4) considered the renal mechanism for potassium conservation to be relatively inefficient, whereas Fourman (5) has demonstrated a U/P ratio of less than 1.0 in the normal human. Depletion of body potassium may be associated with hypokalemic alkalosis (1), shifts of sodium into potass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
1

Year Published

1955
1955
1992
1992

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 14 publications
1
22
1
Order By: Relevance
“…A readily demonstrable defect in renal tubular function occurred with degrees of potassium depletion tolerated by other body cells with apparent impunity (27)(28)(29). This may be ascribed to an apparent critical vulnerability of the renal tubular epithelium to potassium deficiency; however, comparable techniques to examine other body cells are lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A readily demonstrable defect in renal tubular function occurred with degrees of potassium depletion tolerated by other body cells with apparent impunity (27)(28)(29). This may be ascribed to an apparent critical vulnerability of the renal tubular epithelium to potassium deficiency; however, comparable techniques to examine other body cells are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The redistribution of body fluids with sodium retention, especially the increased extracellular volume that attends potassium deficiency (27)(28)(29) if sodium is not restricted, could be expected to alter the excretion of a water load. Extrarenal factors, such as production and renal responsiveness to aldosterone and changes in body fluid volumes, may be produced by potassium depletion and may exert unknown effects on these experiments.…”
Section: Discussionmentioning
confidence: 99%
“…servation of potassium, hypokalemia may occur with The results of the present studies indicate that both in (21)(22)(23)(24)(25)(26)(27). Some of the subjects represented by 0 were mildly alkalotic and were excreting significant amounts of urinary bicarbonate (27) ; the subj ects represented by + were moderately alkalotic and were excreting more than 50 mEq of urinary bicarbonate daily (22) ; the subjects represented by X were given large amounts of desoxycorticosterone after hypokalemia supervened (27 (14,36,37).…”
Section: Methodsmentioning
confidence: 77%
“…In studies 1-5, in which arterial pH remained normal throughout (7.38-7.42 magnitude of negative potassium balance appeared to be modest as judged from cumulative urinary losses of potassium. When dietary potassium is restricted in most normal subjects, the occurrence of hypokalemia is less rapid, despite relatively greater cumulative urinary losses of potassium (21)(22)(23)(24)(25)(26). But in normal subjects, in contrast to the patients studied with RTA, urinary excretion of potassium decreases to less than 40 mEq/day when hypokalemia occurs, even when it occurs rapidly and despite relatively modest negative potassium balance (27).…”
Section: Methodsmentioning
confidence: 99%
“…Since then other workers have shown that significant degrees of potassium depletion, i.e., 5 per cent of the body stores, may be induced without production of either hypochloremia or alkalosis. 12 ' 13 Abstraction of chloride, sodium loading, or interference with sodium excretion following ACTH did. Data are too limited at present to assert that hypochloremic alkalosis associated with potassium losses always represents chloride deficiency or necessitates sodium loading.…”
mentioning
confidence: 99%